Dampak Hukum Berlakunya Perjanjian Perkawinan (Postnuptial Agreement) Sejak Tanggal Akta Terhadap Harta Bersama dalam Perkawinan - Erlina, Erlina; Fathinnuddin, Muhammad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2025)
A prenuptial agreement is a legal instrument that grants married couples the authority to regulate the ownership of assets, rights, and obligations during marriage. In Indonesia’s legal system, its provisions have evolved from the Civil Code and Law Number 1 of 1974 on Marriage to the Constitutional Court Decision Number 69/PUU-XIII/2015. This decision is a significant milestone as it allows the agreement to be made not only before but also after the marriage. A postnuptial agreement may take effect either from the date of marriage or from the date the deed is signed. If it takes effect from the deed date, assets acquired beforehand remain as joint property, which carries legal implications, particularly concerning land ownership by foreign spouses. This paper discusses the legal development of postnuptial agreements and their impact on asset management, recommending that notaries explain potential legal risks and consider applying the agreement from the start of the marriage to prevent disputes.